Analisa Kinerja Usaha Pemasaran Pakan Ayam Pada Rajawali Feed Centre Padang - Fitrini Fitrini (Jurnal Peternakan Indonesia (Indonesian Journal of Animal Science), 2006)
The aims of the present research were to evaluate the management and financial performance of poultry shop. Data or information were directly collected by visiting and interviewing of Rajawali Feed Centre Padang. Data collected included: daily management practices, kinds of produk sold, cost of handling, transport dan storage and organization cost. Financial data were analyzed for Current Ratio, Quick Ratio, Solvability Ratio ond Sales Turn Over. Results showed that Rajawali Feed Centre basicly have a good financing and management performance. Financing performance (Current Ratio : 298,13% ; Quick Ratio : 111,80% ; Solvability Ratio : 500% and Sales Turn Over : 23,20). According to financing and management performance analysis of this business, Rajawali Feed Centre have a good development prospect.